Gender Differences in Participation and Achievement in Science: Implications and Intervention Strategies for Scientific and Technological Development in the Caribbean - Ogunkola, Babalola J.; Garnerâ€“Oâ€™Neale, Leah (Richtmann Publishing, 2013)
Gender differences in science have received serious attention in science education research for the last two decades. Boysand girls have been compared on various variables such as achievement, attitude, motivation, interest, and performancebehaviors. Moreover, the differences have been linked with unequal representation of men and women in science andtechnology â€“ related careers indicating levels of contributions of men and women to national development. Therefore, thispaper contends that it is difficult to address the issue of national development particularly in science and technology withoutrecourse to the gender factor. Specifically, the 1995 Commonwealth Plan of Action on gender and development, indicates thatâ€œthe Commonwealth shall work towards a world in which women and men have equal rights and opportunities in all stages oftheir lives to express their creativity in all fields of human endeavour and in which women are respected and valued as equaland able partners in establishing values of social justiceâ€. This paper poses and answers these questions: (a) What is thepattern of gender differences in science achievement internationally and in the Caribbean? (b) What are the possibleexplanations for gender differences in science achievement internationally and in the Caribbean? (c) What are the effects ofgender differentials in science on national development? (d) What are the possible intervention strategies towards genderbalance in science achievement? This paper presents answers to these questions using reports of meta-analysis of scienceeducation research and goes ahead to offer suggestions for action as to how gender gaps can be bridged in the Caribbean inorder to ensure contributions of both men and women to regional scientific and technological development.